"In Love at First Sight Completely, Hopelessly, and Forever with Chinese Art": The Eugene and Agnes Meyer Collection of Chinese Art at the Freer Gallery of Art. Issue 3 (September 2014) - Chudzicka, Dorota
The Agnes and Eugene Meyer collection of Chinese bronzes, paintings, and sculptures came to the Freer Gallery of Art through Agnes Meyer's donations in the 1960s, her bequest in 1971—the largest single expansion of the Freer Gallery's collection to date—and her children's donations in the 1990s and 2000s. Research on this collection reveals that the Meyers, who were active supporters of avant-garde art in New York, also acquired their Asian collection in the years between 1910–20. The study of the Meyer collection, and the circumstances of its acquisition, provides a fascinating look at the rapidly expanding Asian art market in the United States in the World War I era, and especially of the influence of Charles Freer on the collectors during this era. Encouraged and guided by Freer, Agnes and Eugene Meyer acquired Chinese art objects from many newly established dealers of Chinese art in the U.S. While the Meyers' personal acquisition activities began to dwindle in the 1920s, Agnes Meyer remained closely involved in shaping the Freer Gallery's collection in subsequent years.